Caffeic acid phenethyl ester suppressed growth and metastasis of nasopharyngeal carcinoma cells by inactivating the NF-κB pathway - Liang Y; Feng G; Wu L; Zhong S; Gao X; Tong Y; Cui W; Qin Y; Xu WQ; Xiao X; Zhang Z; Huang G; et al. (Dove Medical Press, 2019)
Yushan Liang,1,2 Guofei Feng,1,2 Liang Wu,3 Suhua Zhong,1,2 Xiaoyu Gao,1,2 Yan Tong,1,2 Wanmeng Cui,1 Yongying Qin,1 WenQing Xu,1 Xue Xiao,1,2 Zhe Zhang,1,2 Guangwu Huang,1,2 Xiaoying Zhou1,41Key laboratory of High-Incidence-Tumor Prevention & Treatment, Ministry of Education, Guangxi Medical University, Nanning, People’s Republic of China; 2Department of Otolaryngology Head & Neck Surgery, First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of China; 3Jiangsu Key Laboratory of Drug Screening, China Pharmaceutical University, Nanjing, People’s Republic of China; 4Life Science Institute, Guangxi Medical University, Nanning, People’s Republic of ChinaPurpose: Caffeic acid phenethyl ester (CAPE) is the main polyphenol extracted from honeybee propolis, which inhibits the growth of several kinds of tumor. This study aimed to assess the inhibitory effect of CAPE in nasopharyngeal carcinoma (NPC), evaluate the synergistic action of CAPE in radiotherapy sensitivity of NPC cell lines and further elucidate the possible molecular mechanism involved.Materials and methods: CCK-8 assay was used to analyze cell proliferation ability. Colony formation assay was used to evaluate the clonogenic ability and radio-sensitiveness of NPC cells by CAPE treatment. Wound-healing and transwell assay were used to assess the motility of cells. The expression of key molecules of the epithelial–mesenchymal transition (EMT) was determined by western blot analysis and changes in radiation sensitivity were measured by colony-formation assay. cDNA microarray analysis was used to determine differentially expressed genes with and without CAPE treatment, with Gene Ontology enrichment of gene function and KEGG pathways determined. Cell cycle and apoptosis were detected by flow cytometry and western blot analysis.Results: CAPE suppressed the viability of NPC cell lines time- and dose-dependently. It induced apoptosis in NPC cells along with decreased expression of Bcl-XL and increased cleavage of PARP and expression of Bax. G1 phase arrest was induced by CAPE with ower expression of CDK4, CDK6, Rb and p-Rb. The migratory and invasive ability of NPC cells was decreased by the EMT pathway. The irradiation sensitivity of NPC cells was enhanced with CAPE treatment. CAPE specifically inhibited nuclear factor κB (NF-κB) signaling pathway by suppressing p65 subunit translocation from cytoplasm to nucleus. CAPE treatment was synergistic with chemotherapy and radiotherapy.Conclusion: CAPE may inhibit the proliferation and metastasis of NPC cells but enhance radiosensitivity in NPC therapy by inhibiting the NF-κB pathway. CAPE could be a potential therapeutic compound for NPC therapy.Keywords: nasopharyngeal carcinoma, CAPE, proliferation, metastasis, NF-κB pathway